LncRNA GAS5 inhibits microglial M2 polarization and exacerbates demyelination. (14th August 2017) - Sun, Dingya; Yu, Zhongwang; Fang, Xue; Liu, Mingdong; Pu, Yingyan; Shao, Qi; Wang, Dan; Zhao, Xiaolin; Huang, Aijun; Xiang, Zhenghua; Zhao, Chao; Franklin, Robin JM; et al.
Abstract: The regulation of inflammation is pivotal for preventing the development or reoccurrence of multiple sclerosis (MS). A biased ratio of high‐M1 versus low‐M2 polarized microglia is a major pathological feature of MS. Here, using microarray screening, we identify the long noncoding RNA (lncRNA) GAS5 as an epigenetic regulator of microglial polarization. Gain‐ and loss‐of‐function studies reveal that GAS5 suppresses microglial M2 polarization. Interference with GAS5 in transplanted microglia attenuates the progression of experimental autoimmune encephalomyelitis (EAE) and promotes remyelination in a lysolecithin‐induced demyelination model. In agreement, higher levels of GAS5 are found in amoeboid‐shaped microglia in MS patients. Further, functional studies demonstrate that GAS5 suppresses transcription of TRF4, a key factor controlling M2 macrophage polarization, by recruiting the polycomb repressive complex 2 (PRC2), thereby inhibiting M2 polarization. Thus, GAS5 may be a promising target for the treatment of demyelinating diseases. Synopsis: A high ratio of M1 versus M2 polarized microglia is a major pathological feature of multiple sclerosis. The lncRNA GAS5 is a negative regulator of M2 polarization, is highly expressed in amoeboid‐shaped microglia of MS patients and promotes demyelination. LncRNA GAS5 is a strong inhibitor of microglial M2 polarization, both in mouse and in human. Interference with GAS5 attenuates the progression of experimental autoimmune encephalomyelitis and promotes remyelination. GAS5 suppresses IRF4 transcription by binding to PRC2. Abstract : A high ratio of M1 versus M2 polarized microglia is a major pathological feature of multiple sclerosis. The lncRNA GAS5 is a negative regulator of M2 polarization, is highly expressed in amoeboid‐shaped microglia of MS patients and promotes demyelination.